The Relationship between Color and Music in the Art of Composer Ede Terényi - COCA, Gabriela (Studia Universitatis Babes-Bolyai Musica, 2023)
From his early youth, the composer lived his whole life under the spell of colors and color combinations. His talent as an artist was already apparent at the age of six, when, in addition to his piano studies, he enjoyed drawing plants and flowers in school notebooks. He kept his first vase, on one side of which he drew a bouquet of flowers sprouting from a heart on a bright pale green background when he was in high school, and on the other side a deer flying through a bush and a pine tree. She always felt a special fascination for the pine tree, seeing it as a symbol, its scent, and its green color as magical. He was similarly attracted to green grassy lawns and the changing colors of autumn leaves, which he saw as a symphony. These childhood experiences are also reflected in his colorful graphics. This paper presents the relationship between color and music in Ede Terényi’s compositions, and the composer’s conception of tonal aesthetics, the relationship between tonalities and colors.